Ideas of Ulrich Beck: Classic Context, Modern Discussion and Possible Synthesis - Kononov, Illya (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2020)
In the second part of the article, the ideas of U. Beck are considered in the context of classical and modern theories. Particular attention is focused on the significance of the heritage of N. Machiavelli and I. Kant for the author of “The Risk Society”. The German sociologist proclaimed himself as machiavellist, but at the same time he often referred to I. Kant. A dilemma arises: how can political cynicism be combined with moral rigor? The article proposes its solution. U. Beck combines the ideas of N. Machiavelli and I. Kant through the concept of republicanism. The ideas of cosmopolitanism were justified by I. Kant and found development in the work of U. Beck. The article shows that Ulrich Beck’s talent is an ability to contextual combinatorics. Apparently, he personally introduced a small number of concepts that became the achievement of sociology ("Second Modern", "meta-game", "meta-power"). U. Beck borrowed the rest of the concepts from other scientists and politicians and put them in his own mental context. But the works of the German sociologist were polemically directed and thereby contributed to the development of sociology. Particular attention in the article is drawn to the U. Beck’s criticism of the concept of postmodernism. The progressive shift in the problem that Beck observes in the concept of the Second Modernity is not just that he proves the continuation of Modernity, but that he establishes its processuality, qualitative changes in it. The article concludes that for the further development of sociology, a synthesis of ideas of the theory of the Second Modernity, world-system analysis, modern Marxist sociology and environmental sociology is desirable. This synthesis is unlikely to be simple. To make it possible, it is necessary to reconstruct the methodological basis of each of these areas in modern sociology.